From morality to metaphysics : the theistic implications of our ethical commitments - Ritchie, Angus (Oxford : Oxford University Press, 2013)
Angus Ritchie offers an argument for the existence of God, which is based on our most fundamental moral beliefs. He argues for the 'deliberative indispensability' of moral realism, and asserts that only theism can adequately explain our capacity for knowledge of objective moral truths.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Keywords: God (Christianity); Religion and ethics